Bullous lung disease and cigarette smoking: A postmortem study - (:unkn) unknown (My University, 2005)
Objectives: Most patients with bullous emphysema are cigarette smokers. This autopsy-based study was performed to assess the relationship between bullous lung disease and smoking in the Turkish population. Methods: One hundred and thirty-one autopsy cases, without any pulmonary injury or known pulmonary disease, and with reliable smoking history, were enrolled. They were divided into two: Group I (non-smokers, n=50, 26 males, and 24 females), and Group II (smokers, n=81, 74 males, and 7 females). Multiple bilateral wedge resections were performed for pathological examination. The relationship between bullous pathology and smoking was investigated. Results: Bullae were found in 6% of group I, and in 40.7% of group II. 32% in group I, and 34.6% in group II had bullous emphysematous pathologies. Overall, 38% in group I, and 75.3% in group II had bullous lung diseases. Bullous lung disease was statistically more common in group II (p=0.087). Conclusion: Even without any respiratory complaint, smoking causes bullous emphysematous pulmonary pathologies. As the incidence of cigarette smoking is high in Turkey, emphysematous changes and bullous lung diseases are expected to be common.
Keywords: Autopsy; Bullous emphysema; Cigarette smoking